ANALISIS PENERAPAN PENCATATAN AKUNTANSI PELAKU UMKM PENGRAJIN BATA MERAH DESA MOJOTAMPING KECAMATAN BANGSAL KABUPATEN MOJOKERTO - Wardhani, Atika Putri; Aziza, Nurna (Journal Accounting International Mount Hope, 2024)
This research will take the object of MSMEs in Mojotamping Village, Bangsal District, the Red Brick industry (Pres MRH). The aim of this research is to find out to what extent MSMEs have knowledge of accounting in their business operations and to analyze accounting records for each transaction. This study uses a qualitative method. Data analysis using retrieval techniques through interviews. The population in this study were MSME actors in the Red Brick industrial sector in Mojotamping Village, Bangsal District. The sample in this study is correspondents who are considered key to providing answers to the research objectives, namely 1 person is assumed to be sufficient to represent the entire population. The results of this research show that MSME actors in the Bata Merah industrial sector have implemented accounting with very simple recording using their respective languages. However, MSMEs still find it difficult to prepare financial reports as they should. It is hoped that this research can increase knowledge about the importance of accounting records to form a financial report. It is hoped that the implications of this research will provide considerations for the government in terms of providing accounting training as an urgency for the business continuity of MSMEs.